Treatment failure in a case of fungal keratitis caused by Pseudallescheria boydii. - Bloom, P. A. (1992)
A case is presented of Pseudallescheria boydii fungal keratitis in an agricultural welder. Treatment with azole antifungal drugs (miconazole and itraconazole) and with penetrating keratoplasty was unsuccessful in eradicating the infection, and eventually the eye was eviscerated.